Anatomy, ploidy level, and essential oil composition of Hyssopus officinalis ʻNikitskiy Beliyʼ in vitro and ex situ - I. V. Bulavin; N. N. Ivanova; N. N. Miroshnichenko; N. M. Saplev; S. A. Feskov (Труды по прикладной ботанике, генетике и селекции)
Background. Clonal micropropagation is a biotechnological method for plant multiplication. The existing data on the structure of organs in vitro, genetic stability, and essential oil composition are limited for Hyssopus officinalis L., so this study was aimead at investigating these aspects under a short period of in vitro culturing.Materials and methods. Plants of Hyssopus officinalis ʻNikitskiy Beliyʼ cultivated ex situ, in vitro and ex vitro were analyzed. Conventional methods were applied to study plant anatomy, ploidy level, and relative DNA content, as well as to extract and analyze essential oil. Statistical analysis was performed using the Past 4.03 software.Results. According to the results obtained, with 6-BAP introduced into MS nutrient medium in optimal concentrations (0.3– 0.5 mg/L), the general in vitro structure of leaf blades in the developed microshoots was similar to those in ex situ plants, while the qualitative and quantitative changes observed were induced by the effect of specific culturing conditions and plant rejuvenation. The analysis of the ploidy level and relative DNA content in the nuclei isolated from the leaf tissue cells of the microshoots ex vitro after adaptation revealed no changes compared to the ex situ leaf parameters. The mass fraction of essential oil and its component composition in the mother plants and ex vitro regenerants were similar.Conclusion. Cultivation of Hyssopus officinalis ʻNikitskiy Beliyʼ microshoots on MS nutrient medium with 6-BAP optimal concentrations promotes morphogenesis without significant deviations in the ploidy level, relative DNA content, essential oil yield, or its component composition. The developed protocol for clonal micropropagation of Hyssopus officinalis ʻNikitskiy Beliyʼ provides clones identical to the ex situ plants.